2017
DOI: 10.5056/jnm16122
|View full text |Cite
|
Sign up to set email alerts
|

Foods Inducing Typical Gastroesophageal Reflux Disease Symptoms in Korea

Abstract: Background/AimsSeveral specific foods are known to precipitate gastroesophageal reflux disease (GERD) symptoms and GERD patients are usually advised to avoid such foods. However, foods consumed daily are quite variable according to regions, cultures, etc. This study was done to elucidate the food items which induce typical GERD symptoms in Korean patients. MethodsOne hundred and twenty-six Korean patients with weekly typical GERD symptoms were asked to mark all food items that induced typical GERD symptoms fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…In the analysis, we noticed that GERD was more common in patients who consumed spicy food twice or more per week (48.9%). Spicy foods can irritate inflamed lower esophageal mucosa that may lead to heartburn as suggested by Choe et al [23] and Alsulobi et al [24]. Other studies do not mention spicy food as a significant factor [25,26].…”
Section: Resultsmentioning
confidence: 98%
“…In the analysis, we noticed that GERD was more common in patients who consumed spicy food twice or more per week (48.9%). Spicy foods can irritate inflamed lower esophageal mucosa that may lead to heartburn as suggested by Choe et al [23] and Alsulobi et al [24]. Other studies do not mention spicy food as a significant factor [25,26].…”
Section: Resultsmentioning
confidence: 98%
“…Current opinions on the relationships between fatty foods, spicy foods, sweets, noodles, and fruits and the onset of RE are inconsistent, with some studies showing such associations [ 14 , 15 , 18 , 19 ] while others could not confirm such associations [ 1 , 3 , 5 , 16 , 17 , 20 ]. Our study found that preferences for sweets, noodles and acidic foods showed positive correlations with RE, while preferences for fried and fatty foods and fruits were not related to the onset of RE.…”
Section: Discussionmentioning
confidence: 99%
“…Sup daging pedas, kue beras, mie ramen, makanan yang digoreng, dan topokki adalah makanan yang sering memicu gejala GERD di Korea. 27 Konsumsi makanan pedas secara berlebihan akan merangsang lambung untuk berkontraksi dan kandungan bubuk cabai tersebut dapat menghilangkan sel epitel pada lapisan mukosa. Apabila mengkonsumsi makanan pedas lebih dari satu kali dalam seminggu selama minimal 6 bulan dan dibiarkan berlangsung lama maka akan menyebabkan iritasi pada mukosa lambung dan…”
Section: Penelitian Ini Dilakukan DI Fakultas Kedokteranunclassified